Achieving high strength, plasticity and conductivity in Cu/Cu-graphene oxide laminated composites with extremely low content of graphene oxide - Yan Zhao; Jiajing Liu; Yubo Zhang; Xin Sun; Wei Wang; Tingju Li (Materials & Design)
Although high-performance graphene/Cu composites can be achieved via introducing the high-content graphene, it is still a challenge to obtain cheap and facile graphene/Cu composites due to their high cost and complex preparation process through existing technologies. Herein, the laminated structure is applied to reduce the overall mass fraction of graphene oxide (GO) and the Cu/Cu-GO laminated composites are designed and prepared through plastic deformation under simple conditions. The pinning effect of GO at grain boundaries results in dislocations accumulation, which provides the driving force for strain-induced grain boundary migration and achieves a good interfacial bonding between Cu and Cu-GO layers. A well-bonded interface induces the interface-affected zone with dislocations pile-up during loading, which significantly improves mechanical properties. The yield strength (YS), ultimate tensile strength (UTS) and uniform elongation of the Cu/Cu-0.3GO-1 laminated composite are up to 377 MPa, 469 MPa and 22.0 %, respectively, with a very low mass fraction of 0.03 % GO. In addition, a nacre-like structure with the oriented arrangement of GO is obtained in Cu-0.3GO layers, which is conductive to carrier transport and leads to a high conductivity of 98.49 %IACS for laminated composites. Moreover, the wear rate is reduced by about 40 % compared to the rolled Cu.